Power Optimization Configuration For Piezoelectric Cantilever Arrays - Bong, Yu Jing; Kok, Swee Leong (EDP Sciences, 2017)
This paper investigates the changes in the output of the piezoelectric cantilever arrays when connected in different configurations. In this research matching load resistance determined and optimum output was measured by connecting the piezoelectric cantilever arrays to resistance ranging from 10 Ω to 1 MΩ while excited by constant vibration source at frequency of 300 Hz and acceleration of 1-g level. The result shows that matching load resistance for one single piezoelectric cantilever is 13 KΩ. When two, three and four cantilevers are connected in series, the matching load resistance is 26 kΩ, 39 kΩ and 52 kΩ respectively. While in parallel connection, matching load resistance reduced to 6.5 kΩ, 4.5 kΩ and 3.5 kΩ for two, three, and four connected cantilevers respectively. In series configuration, the voltage output produced is much higher as compared to the piezoelectric cantilever arrays that are connected in parallel connection. The voltage output of the piezoelectric cantilever increased from 3.41V to 6.09V when it is connected in series configuration with same polarity. Whereas in term of power output, piezoelectric cantilever arrays in parallel configuration produce higher power output as compared to piezoelectric cantilever arrays in series connection. The maximum power increased from 272μW to 521μW when two cantilevers are connected in parallel configuration with same polarity.